Hyalocyte functions and immunology. (4th July 2022) - Boneva, Stefaniya K; Wolf, Julian; Wieghofer, Peter; Sebag, J; Lange, Clemens AK
ABSTRACT: Introduction: Vitreous hyalocyte functions have only recently been explored in-depth. These macrophage-like cells play critical roles in immunologic surveillance and physiology of the developing and adult eye. Areas covered: Hyaloid vasculature involution during embryogenesis, synthesis and degradation of vitreous components during development and aging, and maintenance of vitreous transparency will be discussed. This article also reviews immunologic features during development and in the adult. Expert opinion: Recent transcriptional analyses have demonstrated that despite similarity to other myeloid cell populations such as microglia and monocyte-derived macrophages, hyalocytes possess a distinct expression profile and molecular signature. Hyalocytes are important in hyaloid vasculature involution during development, ocular immune privilege and immune surveillance, synthesis and degradation of vitreous components, as well as migration and phagocytic activity during adulthood.